The origin of German tragic drama - Benjamin, Walter (Verso, 1998)
In this text, the author offers a theoretical introduction to the nature of the baroque art of the 16th and 17th centuries, concentrating on the "Trauerspiel". He also comments on the engravings of Durer and the theatre of Calderon and Shakepeare. Baroque tragedy, he argues, was distinguished from classical tragedy by its shift from myth into history.